Pengaruh Etika Bisnis Islam Kualitas Produk Keberagaman Produk Terhadap Keputusan Konsumen Membeli Produk Emina (AT TAWAZUN: Jurnal Ekonomi Islam, 2023)
The purpose of this study is to find out how the influence of Islamic business ethics on buying decisions, how product quality affects buying decisions and how the diversity of product variants affects buying decisions. The research used by the author is a quantitative type research. Quantitative research is a research that is objective, includes the collection and analysis of quantitative data and uses statistical testing methods. Based on the t test value on the Islamic business ethics variable of 2.296 with a sig. 0.22 which means it has a positive effect on buying decisions, the t test value on the product quality variable is 3,903 with a significant value of 0.000 which means it has a positive effect on buying decisions, the t test value on the product diversity variable is 8.283 with a significant value of 0.000 which means it has a positive effect on buying decision. In addition, the value of the R2 test conducted in this study was 0.459 or 45.9%, this value illustrates the effect of Islamic business ethics on product quality and product diversity on purchases of 14.5%.